Avaliação de um sistema de detecção de radiações ionizantes utilizando diodo PIN para controle de fontes orfãs - Jakubiak, Raisa Requi (2019)
Nuclear and radioactive material smuggling pose a great challenge for intelligence agencies worldwide since the 1990’s. Nuclear and radioactive material security has detection as one of its cornerstones. Therefore, the present work presents the evaluation of a PIN diode-based system as far as its capacity of detecting gamma radiation from radioactive isotopes is concerned, as well as its suitability for further use as an auxiliary equipment for public security in training and orphan sources control. Six diodes were tested. They were chosen according to their peak sensitivity and detection range, which are compatible with the energy range studied X ray and gamma. Sensors were exposed to four different scenarios: diagnostic range X rays, with several voltage (kV) and current (mAs) arrangements, in order to confirm if the system was operating properly; X ray pulses from an industrial X ray equipment, for qualitative investigation; Am-241, Na-22, Sr-90 e Co-60 sources used for didactic purposes and, finally, commercial Cs-137 e Ir-192 sources. It was possible to characterize X ray photons detection for all kV and mAs combinations, for 100% diodes tested. For measurements with radioactive sources, however, it is clear that the system is not capable of detecting gamma photons generated due to the studied sources radioactive decay. Although some voltage peaks can be observed, it is not possible to characterize them as detection due to their random nature. The problem was firstly assigned to the low activity of the analysed didactic sources. Nevertheless, after the experiments using the Ir-192 industrial irradiator, the problem was assigned to silicon features as a gamma detector. Finally, this study concludes that the evaluated system can be used for measurements with X rays, but offers no suitable sensitivity to be used in tracking radionuclides.